ELEMENTAL SULFUR IN DRAIN SEDIMENTS ASSOCIATED WITH ACID SULFATE SOILS - Burton E.D.; Bush R.T.; Sullivan L.A. (My University, 2006)
This paper reports the abundance of elemental S in drain sediments associated with acid sulfate soils. The sediments exhibited near-neutral pH (5.97-7.27), high concentrations of pore-water Fe2+ (1.37-15.9 mM) and abundant oxalate-extractable Fe (up to 4300 μmol g-1). Maximum acid-volatile sulfide (AVS) concentrations in each sediment profile were high (118-1019 μmol g-1), with AVS often exceeding pyrite-S. Elemental S occurred at concentrations of 13-396 μmol g-1, with the higher concentrations exceeding previous concentrations reported for other sedimentary systems. Up to 62% of reduced inorganic S near the sediment/water interface was present as elemental S, due to reaction between AVS and oxidants such as O2 and Fe(III). Significant correlation (r = 0.74; P < 0.05) between elemental S and oxalate-extractable Fe(III) is indicative of elemental S formation by in situ oxidation of AVS. The results indicate that AVS oxidation in near-surface sediments is dynamic in acidified coastal floodplain drains, causing elemental S to be a quantitatively important intermediate S fraction. Transformations of elemental S may therefore strongly influence water quality in ASS landscapes. © 2006 Elsevier Ltd. All rights reserved.